The relationship between motivatison factors and job satisfaction among employee at government sector organization - Syaifarina, Kamaruddin (Universiti Malaysia Sarawak (UNIMAS), 2019)
This study is aimed to determine the relationship between training, rewards and job security with job satisfaction. This study was done in all of the employee in Yayasan Sarawak. A total of 96 set of questionnaires were distributed. However, only 80 set of questionnaires were completed and returned. Data obtained were analysed by using SPSS to determine the relationship between training, rewards and job security, and the job satisfaction. The result also showed that there is also a significant relationship for training, rewards and job security. Besides, job satisfaction is only variable that had mediating effect on the training, rewards and job security. This result indicates that training, rewards and job security can improve the job satisfaction among employee. The findings from this study are beneficial to all manager to find effective ways to improve their employees in order to improve their business as well.